The memory binding test can anticipate Alzheimer’s disease diagnosis at an early preclinical stage: a longitudinal study in the INSIGHTpreAD cohort - Raposo Pereira, Filipa; George, Nathalie; Dalla Barba, Gianfranco; Dubois, Bruno; La Corte, Valentina (Frontiers in Aging Neuroscience, 2024)
Introduction Anticipating the diagnosis of Alzheimer’s disease (AD) at an early asymptomatic at-risk stage, where therapeutics can more effectively delay conscious cognitive decline, is currently among the biggest challenges in the field. Herein, we aimed to compare the capacity of the Memory Binding Test (MBT) with the official diagnostic tool, the Free and Cued Selective Reminding Test (FCSRT), to anticipate AD diagnosis at an early preclinical stage based on the associative memory component of MBT (binding), suggested as more sensitive to the emergence of subtle episodic memory (EM) deficits (AD hallmark). Methods We assessed the tests performance longitudinally (over 5 years) in 263 cognitively-normal elderly individuals at risk of AD (>6 months of subjective memory complaints) using linear mixed-effect models controlled for age, sex, and education. We stratified participants in 2 models: amyloid-β (Aβ)/neurodegeneration (N) model, assessing Aβ burden and neurodegeneration effect [3 groups: controls (Aβ-/N-); stable/N- (Aβ+); stable/N+ (Aβ+)]; and the stable/progressors model, assessing progression to prodromal-AD effect [2 groups: stable (Aβ+); progressors (Aβ+)], based on 15 subjects who progressed to AD during follow-up (excluded once diagnosed). Results Aβ burden was associated with significantly less MBT-intrusions, while Aβ burden and neurodegeneration together, with the most. Progression status had a strong negative effect on both tests performance. When compared with the FCSRT, the MBT seems to anticipate diagnosis based on a worst performance in a higher number of scores (including binding) in at least a year. Discussion Anticipation of diagnosis to an asymptomatic at-risk stage, while participants remain cognitively-normal according to FCSRT cut-offs and unaware of objective EM deficits, has the potential to delay the onset of AD-linked cognitive decline by applying promising therapeutics before decline becomes too advanced.